A dual-band efficient circularly polarized rectenna for RF energy harvesting systems - Ang, Ming Jie (2021)
A multilayered circularly polarized (CP), dual-band, stacked slit-/slotted-patch antenna with compact size and with compact rectifier is offered for RF energy harvesting systems. The compact dual-band CP antenna size is able to achieve by stacking slotted-circular-patch (SCP) on the substrate above the tapered-slit-octagon patch (TSOP). Dual-band CP radiation is realized by stacking the SCP on the TSOP and the microstrip feedline with metallic-via to SCP. Eight-tapered-slit with length difference of 6.25% are embedded along the octagonal directions symmetrically on the TSOP from the patch's center and two unequal size circular slots are embedded in diagonal axis onto SCP to produce dual-orthogonal modes with almost equal magnitude for CP waves. The designed antenna is realized measured gain of greater than 5.2 dBic across the band (0.908-0.922 GHz) with maximum gain of 5.41 dBic at 0.918 GHz and gain of greater than 6.14 dBic across the band (2.35-2.50 GHz) with maximum gain of 7.94 dBic at 2.485 GHz. An overall antenna volume is 0.36λ ₀ × 0.36λ ₀ × 0.026λ ₀ (λ ₀ is free space wavelength at 0.9 GHz). A compact composite right-/left-handed (CRLH) based rectifier with dual-band at 0.9 and 2.45 GHz is designed, prototyped, and measured. The right-handed (RH) part of the CRLH transmission line (TL) is formed by a microstrip line. The left-handed (LH) part of the CRLH-TL is formed by lumped components. The measured RF-DC conversion efficiency is 43% at 0.9 GHz and 39% at 2.45 GHz with rectifier size of 0.18λ ₀ × 0.075λ ₀ × 0.0002λ ₀ at 0.9 GHz.